Representasi Bullying di Sekolah Dasar: Studi Kasus di Sekolah Model dan Pembina - Ferry Aristya (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2020)
The purpose of this study is to represent bullying in one of the Model elementary schools in Sragen. This research adopts a qualitative approach, which is a case study, to reach the goal. The research subjects are all teachers and students of Model Elementary Schools. Data collected by observation and in-depth interviews. The results of this study describe (1) the impact shown by victims of both female and male gender and audience reactions; (2) forms of bullying; 3) handling bullying. Detailed results and discussion can be seen in this article. Keywords: representation, bullying, preventive, elementary school